The Effectiveness of Bullying Curriculum for Prevention and Management of Bullying in School-Aged Children - Nur Eni Lestari; Yeni Koto (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2019)
Introduction: Bullying is still a problem and continues to increase especially in school-aged children. If cases of bullying do not get any immediate treatment, it will cause various problems from psychological, psychosomatic, social, academic issues, and even present a risk of suicide. The purpose of this study was to determine the effectiveness of bullying curriculum for prevention and management of bullying in school-aged children. Methods: The study used a quantitative study method with a quasi-experimental of pre and post-test without control group design. The population of this study was students of grade-five in one of primary school in Jakarta. The samples of this study used total sampling consisting of 30 respondents. The instrument of this study used the instrument of bullying that was modified by the researchers and has passed the validity and reliability test. The analysis of this study used McNemar test. Results: The result of this study shows that there were bullying incidents occurred for as much as 100% before the intervention and as much as 60% after the intervention. The result of bivariate test of this study shows the value of p=0.000. Conclusions: The implementation of curriculum of bullying is effective for prevention and management of bullying in school-aged children.